Iodine-catalyzed aromatization of tetrahydrocarbazoles and its utility in the synthesis of glycozoline and murrayafoline A: a combined experimental and computational investigation - Humne, Vivek T.; Dangat, Yuvraj B.; Vanka, Kumar; Lokhande, Pradeep (Organic & Biomolecular Chemistry, 2014)
A new protocol for the aromatization of tetrahydrocarbazoles has been achieved using a catalytic amount of iodine, giving high yields. The role of iodine in the aromatization has been explained by DFT, and its wide scope is extended to the total synthesis of glycozoline and murrayafoline A. This method has proven to be tolerant of a broad range of functional groups.

Radical beckmann rearrangement and its application in the formal total synthesis of antimalarial natural product isocryptolepine via C-H activation - Mahajan, Pankaj S.; Humne, Vivek T.; Tanpure, Subhash D.; Mhaske, Santosh B. (Organic Letters, 2016)
The Beckmann rearrangement of ketoximes, mediated by ammonium persulfate-dimethyl sulfoxide as a reagent, has been achieved under neutral conditions. Based on the radical trapping and O-18-labeling experiments, the transformation follows a mechanism involving a radical pathway. The scope and generality of the developed protocol has been demonstrated by 19 examples. The developed protocol and Pd-catalyzed intramolecular double C-H activation were used as key steps in the formal total synthesis of antimalarial natural product isocryptolepine.

Achmatowicz reaction: A versatile tool in bioactive natural products synthesis - Mahajan, Pankaj S.; Humne, Vivek T.; Mhaske, Santosh B. (Current Organic Chemistry, 2017)
Achmatowicz reaction has emerged as an efficient tool in organic synthesis since its discovery in 1971 by Achmatowicz Jr. The original protocol went through several advantageous variations. Biocatalytic and metal catalyzed versions of this reaction are some of the significant achievements, which further enhanced its effectiveness. The pyranone product of the Achmatowicz reaction is a versatile building block for the synthesis of bioactive scaffolds, drugs and natural products. The present review covers the application of the Achmatowicz reaction in the synthesis of natural products and bioactive molecules reported from 1971 to date. It has been divided into seven sections on the basis of the core structures of the natural products synthesized utilizing the Achmatowicz reaction. We believe that this comprehensive review will attract many more organic chemists to explore its utility in organic synthesis, especially in the synthesis of bioactive natural products as well as drugs in their efficient and atom economical synthesis.
Keywords: Achmatowicz reaction; carbohydrates; Furanols; Natural products; pyranones; Total synthesis

Direct oxidation of bromo-derived Fischer-Borsche oxo-ring using molecular iodine with combined experimental and computational study - Humne, Vivek T.; Ghom, Monica H.; Naykode, Mahavir S.; Dangat, Yuvraj; Vanka, Kumar; Lokhande, Pradeep (Organic & Biomolecular Chemistry, 2022)
A direct oxidation of the bromo-derived Fischer-Borsche oxo-ring leading to carbazolequinone has been developed by using molecular iodine. This unprecedented transformation has been used for the modular synthesis of the anti-cardiotonic agent murrayaquinone. Furthermore, the present method has been generalized to a broad range of functional groups, with good to excellent yield.

Copper-mediated [3+2] oxidative cyclization of oxime acetate and its utility in the formal synthesis of fentiazac - Jadhao, Nitin L.; Musale, Harish B.; Gajbhiye, Jayant M.; Humne, Vivek T. (Organic and biomolecular chemistry, 2024)
A new protocol for the direct synthesis of 2-aminothiazole has been developed from oxime acetate and readily available sodium thiocyanate using a copper catalyst. The present transformation has good functional group tolerance. Various thiazoles were smoothly synthesized in good to excellent yields. The applicability of the present method has been extended to the formal synthesis of the non-steroidal and anti-inflammatory drug, fentiazac via the Sandmeyer reaction and Suzuki coupling. The direct synthesis of 2-aminothiazole has been developed from oxime acetate using a copper catalyst. The applicability of the present method is used in the formal synthesis of fentiazac.
Keywords: Biological evaluation; C-H functionalization; Vinylazides